The Influence of Social Media To Religious Student Generation Z at Medan State University - Timanta Agustina Br Purba; Guslina Wahyuningsih; Sheshilia Putri Damanik; Naila Synta Ramadani; Hapni Laila Siregar (Sean Institute, 2024)
The influence of social media to religious student Generation Z refers to the way in which these digital platforms to form understanding, practice, and identity religious they. As the growing generation in the era of technology, students This using social media For access information religious, interact with community, and express belief they. Research This aiming For to study social media influence to religious students at Medan State University. The type of research conducted in studies This is descriptive with approach mixture, namely quantitative and qualitative. Research results show that there is influence significant positive between social media use and improvement knowledge as well as practice religious students. However, it was also found existence risk decline values religious consequence content negatives circulating on social media. Research This recommend the need more education Good about media literacy for students, so that they can utilizing social media as tool For strengthen faith and values religious they.